Induction of Unbalanced Growth and Death of Streptococcus sanguis by Oxygen - Eisenberg, Roselyn J. (1973)
Streptococcus sanguis has normal streptococcal morphology when grown in a nitrogen atmosphere but undergoes gross morphological alterations when grown in the presence of oxygen (O cells). Studies were made of the relationship between the development of pleomorphism and the loss of viability which accompanied it in O cultures of S. sanguis. The development of pleomorphism appears to involve two events. The first step, or triggering event, occurs in log-phase cultures in the presence of oxygen. The second step, or manifestation of pleomorphism, occurs at stationary phase in the presence or absence of oxygen. The loss of viability appears to be related both to the length of time the culture is exposed to oxygen as well as to a specific event which occurs at the transition from log to stationary phase. Oxygen also induced a state of unbalanced growth in S. sanguis in which the proportions of deoxyribonucleic acid, ribonucleic acid, and protein synthesized were altered. The relationship of these alterations to the development of pleomorphism is discussed.